Proceedings of the 4th Conference on Innovations in Theoretical Computer Science 2013
DOI: 10.1145/2422436.2422455
|View full text |Cite
|
Sign up to set email alerts
|

The garden-hose model

Abstract: Abstract. We define a new model of communication complexity, called the garden-hose model. Informally, the garden-hose complexity of a function f : {0, 1} n × {0, 1} n → {0, 1} is given by the minimal number of water pipes that need to be shared between two parties, Alice and Bob, in order for them to compute the function f as follows: Alice connects her ends of the pipes in a way that is determined solely by her input x ∈ {0, 1} n and, similarly, Bob connects his ends of the pipes in a way that is determined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(75 citation statements)
references
References 25 publications
4
71
0
Order By: Relevance
“…Can we show security in the bounded-quantum-storage model [21] where adversaries are limited to store, say, a linear fraction of the communicated qubits, thus restricting the amount of available entanglement? These questions do remain open in general but have already triggered quite a bit of follow-up work [3,11,46] providing partial answers (see section 1.3 for details). Proof.…”
Section: Conclusion Discussion and Open Questionsmentioning
confidence: 99%
“…Can we show security in the bounded-quantum-storage model [21] where adversaries are limited to store, say, a linear fraction of the communicated qubits, thus restricting the amount of available entanglement? These questions do remain open in general but have already triggered quite a bit of follow-up work [3,11,46] providing partial answers (see section 1.3 for details). Proof.…”
Section: Conclusion Discussion and Open Questionsmentioning
confidence: 99%
“…Proof. We refer to this LOBC protocol as U2E, and it is similar in spirit to the protocol of Vaidman and Buhrman et al [11], [15]. Following the terminology of Ref.…”
Section: A Two-qubit Gatesmentioning
confidence: 99%
“…Following the terminology of Ref. [11], we refer to teleportation * as the standard teleportation protocol except with no classical communication and no Pauli correction on the receiving end. Protocol U2E: Two ebit protocol for U ∈ L • Input an arbitrary two-qubit state |ψ AB .…”
Section: A Two-qubit Gatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A different class of position-based verification protocols based on the nonlocal computation of Boolean functions was introduced by Buhrman et al in [13], for which they suggested a new type of attacks based on the Gardenhose complexity of the Boolean function. They showed in particular that finding an explicit Boolean function with polynomial circuit complexity (so that the honest prover can compute it) but exponential attack complexity in the garden-hose model is at least as difficult as separating the classes of languages P and L, corresponding respectively to decision problems decidable in polynomial time or logarithmic space.…”
Section: Introductionmentioning
confidence: 99%